1997
DOI: 10.1007/s002030050508
|View full text |Cite
|
Sign up to set email alerts
|

Molybdate transport and regulation in bacteria

Abstract: Molybdate is transported in bacteria by a high-affinity transport system composed of a periplasmic binding protein, an integral membrane protein, and an energizer protein. These three proteins are coded by modA, modB, and modC genes, respectively. The ModA, ModB, and ModC proteins from various organisms (Escherichia coli, Haemophilus influenzae, Azotobacter vinelandii, and Rhodobacter capsulatus) are very similar. The lowest Km value reported for molybdate in the molybdate transport process is approximately 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
142
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(146 citation statements)
references
References 16 publications
2
142
0
2
Order By: Relevance
“…This was a somewhat surprising observation because genetic and biochemical studies in E. coli have implied the involvement of the MogA and MoeA gene products in cofactor biosynthesis. It has been proposed that molybdenum, which enters the cell as the stable oxyanion molybdate by a high affinity molybdate transport system (19), undergoes some type of modification prior to incorporation into MPT within the cell. For example, a role for the MoeA protein in generating a thiomolybdenum species that might be used in Moco biosynthesis has been suggested (20).…”
Section: Discussionmentioning
confidence: 99%
“…This was a somewhat surprising observation because genetic and biochemical studies in E. coli have implied the involvement of the MogA and MoeA gene products in cofactor biosynthesis. It has been proposed that molybdenum, which enters the cell as the stable oxyanion molybdate by a high affinity molybdate transport system (19), undergoes some type of modification prior to incorporation into MPT within the cell. For example, a role for the MoeA protein in generating a thiomolybdenum species that might be used in Moco biosynthesis has been suggested (20).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a number of genes encoding proteins have been shown to be involved in bacterial resistance to such heavy metals as cobalt, zinc, cadmium, arsenic, copper, molybdenum and silver (Nies, 1995(Nies, , 1999Grunden and Shanmugam, 1997;Rensing et al, 1997Rensing et al, , 1999Brown et al, 2002;Parro and Moreno-Paz, 2003;Zahalak et al, 2004;Basim et al, 2005;Bencheikh-Latmani et al, 2005;Braz and Marques, 2005;Hu et al, 2005;Methe et al, 2005;Permina et al, 2006) and had higher transcript levels in sediment-grown cells (Table 7).…”
Section: Locus Idmentioning
confidence: 99%
“…However, increased expression of the molybdate ABC type transporter genes, modA, modB and modC (Table 7), might also be explained by the fact that there is an increased demand for molybdenum under nitrogenfixing conditions. Earlier studies have shown that increased expression of molybdenum transporter genes is frequently associated with nitrogen-fixing conditions, because molybdenum is an essential component of nitrogenase proteins involved in nitrogen fixation (Grunden and Shanmugam, 1997;Parro and Moreno-Paz, 2003;Zahalak et al, 2004).…”
Section: Locus Idmentioning
confidence: 99%
“…The molybdate uptake system has best been characterized in Escherichia coli, in which incorporation of molybdate by the cell is mediated by a high-affinity ABCtype transport system encoded by the modABC genes. ModA binds molybdate in the periplasm, ModB is the transmembrane component of the permease, and ModC provides the energizer function on the cytoplasmic side of the membrane (for reviews see Grunden & Shanmugam, 1997;Self et al, 2001). Similar systems for molybdate transport have been characterized in Rhodobacter capsulatus (Wang et al, 1993), Azotobacter vinelandii (Luque et al, 1993;Mouncey et al, 1995Mouncey et al, , 1996, Staphylococcus carnosus (Neubauer et al, 1999) and Anabaena variabilis (Thiel et al, 2002;Zahalak et al, 2004).…”
Section: Introductionmentioning
confidence: 95%